Investigation of auto-ignition of several single fuels - Firmansyaha, (EDP Sciences, 2014)
HCCI operating principals have been widely investigated yet the uncontrollable combustion of HCCI is the major obstacle in its development. This paper is trying to increase the understanding on the auto-ignition and combustion process of several fuels to be applied in HCCI combustion system. The investigation includes the combustion behavior of 4 fuels, gasoline (RON95), diesel, n-heptane, isooctane, The investigation was done in constant volume chamber with elevated temperature (800Â°C). Four lambdas were tested for each fuel namely 0.8, 1, 1.2 and 2. It is found that these fuels can be categorized into two major categories based on combustion characteristics, homogeneous and diffusive combustion. Gasoline and isooctane, homogeneous combustion, shows almost the same behavior where the increase in lambda will increase the combustion delay even though isooctane shows much longer delayed compared to gasoline. While diesel and n-heptane, diffusive combustion, has no ignition delay yet showing different behavior on the later parts of the combustion where diesel effecting 10-90 combustion stage while n-heptane on 90-100. Â© 2014 Owned by the authors, published by EDP Sciences.